Robespierre and the Festival of the Supreme Being : the search for a republican morality - Smyth, Jonathan A. (Studies in modern French history., 2016)
Maximilien Robespierre declared that 20 Prairial Year II (8 June 1794) would be a national day of celebration to inaugurate the state religion of the new French Republic, the Cult of the Supreme Being. This book explores Robespierre's vision and the events held across France on this day, to redefine the importance of the Festival of the Supreme Being in the development of the Revolution.